2019
DOI: 10.1523/jneurosci.1512-18.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Two brains in action: Joint-action coding in the primate frontal cortex

Abstract: Daily life often requires the coordination of our actions with those of another partner. After 50 years (1968 -2018) of behavioral neurophysiology of motor control, the neural mechanisms that allow such coordination in primates are unknown. We studied this issue by recording cell activity simultaneously from dorsal premotor cortex (PMd) of two male interacting monkeys trained to coordinate their hand forces to achieve a common goal. We found a population of "joint-action cells" that discharged preferentially w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…As a final neurobiological consideration, our results highlight that the very same lvPMc, belonging to the "mirror" motor system (Rizzolatti and Sinigaglia 2016), contributes to the deciphering of motor goals beyond mere low-level movement imitation. A recent neurophysiological study on nonhuman primates (Ferrari-Toniolo et al, 2019) showed that there is a population of left premotor neurons that preferentially discharge when a monkey cooperates with a partner to achieve a motor goal, independently of the specific visual input that the monkey receives at a given moment ( Ferrari-Toniolo et al, 2019): this is in line with our suggestion that that the activity of premotor regions might be shaped by social motor experience and acquire the possibility to code higher-order "joint" motor representations.…”
Section: Discussionsupporting
confidence: 88%
“…As a final neurobiological consideration, our results highlight that the very same lvPMc, belonging to the "mirror" motor system (Rizzolatti and Sinigaglia 2016), contributes to the deciphering of motor goals beyond mere low-level movement imitation. A recent neurophysiological study on nonhuman primates (Ferrari-Toniolo et al, 2019) showed that there is a population of left premotor neurons that preferentially discharge when a monkey cooperates with a partner to achieve a motor goal, independently of the specific visual input that the monkey receives at a given moment ( Ferrari-Toniolo et al, 2019): this is in line with our suggestion that that the activity of premotor regions might be shaped by social motor experience and acquire the possibility to code higher-order "joint" motor representations.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, this neural mechanism has recently been reported by Thornton et al (2019), who found that the adjustment of current social behavior based on the prediction of the other's future mental state, depended on the action of the medial prefrontal cortex. Similar findings have been found in pairs of monkeys that perform cooperative tasks (Ferrari-Toniolo et al, 2019). Specifically, a unique set of dorsal premotor neurons called "joint-action cells" was found to discharge preferentially during cooperative tasks involving interactive visuomotor coordination between co-acting monkeys.…”
Section: Gamma Interbrain Coupling As a Marker Of Prosocial Behaviorsupporting
confidence: 78%
“…Our and others’ previous results suggest that this interactivity-dependent modulation of action observation might depend on a modulation of the brain activity in fronto-parietal areas 51 – 59 , see also Ref. 60 . Specifically, in the present paradigm, the left ventral premotor cortex might play a critical role 16 , because it is responsible for goal predictions for hand movements in humans 61 , 62 and non-human primates 63 , 64 .…”
Section: Discussionsupporting
confidence: 55%